(untitled) (Research, Society and Development, 2021)
Chiari’s malformation is within the spectrum of congenital abnormalities of the central nervous system (CNS). It is characterized by a complex deformity of the posterior fossa associated almost always with a malformation of the spine. Chiari malformation is still a subject of little evidence in literature, where new studies on this parameter may trigger influences for researchers in the field. The objectives of this study were to describe the main alterations found in the nervous system in individuals with Chiari malformation. It is a literature review study. The following descriptors were used for the search: Chiari malformation, Posterior Pit and Craniovertebral Junction (together and separately). In the selection criteria, full articles were chosen for the period: 2016 - 2019, in the languages: Portuguese and English. The searches were made in the databases: Scielo, Pubmed and Google academic. The articles were selected first by title, then by abstract, and finally by full reading. Based on the established criteria, 3 articles were selected that contemplate the theme. The literature shows that the most suggestive brain alterations of this pathology are cerebellar abnormalities such as caudal displacement of the bridge, IV ventricle and bulb; medullary torsion; IV ventricle in abnormal shape and hypoplasia of the cerebellum tent and mesencephalic ceiling. It is noticeable that Chiari’s malformation can cause alterations that can vary from lighter to more severe. New studies are needed on this subject, as well as solutions to improve the quality of life of patients affected by this syndrome.